KUALITAS PELAYANAN SEBAGAI DETERMINAN KEPUASAN PELANGGAN JASA TRANSPORTASI GRAB BIKE DI YOGYAKARTA - Ramadhan, Fajar; Setyono, Hendro (Jurnal Fokus Manajemen Bisnis, 2019)
This  research  aims  to  analyze  the  influence  of  the  quality  of  service  of customer  satisfaction  on  service  businesses  Grab-Bike  transport  in  Yogyakarta. This  research  uses  the  five  independent  variables  i.e.  tangible,  reliability, responsiveness,  assurance  and  emphaty  with  one  dependent  variable  i.e. consumer  satisfaction.  After  a  review  of  the  literature  as  well  as  field  and preparation  of  the  hypothesis,  the  data  in  this  study  were  collected  through  the dissemination  of  a  questionnaire  to  70  people  who  never  use  the  Grab-Bike transport  as  research  samples.  Sampling  technique  used  is  a  Non  probability sampling  method  sampling  incidental.  Methods  of  data  analysis  used  is  the quantitative analysis that is test validity and reliability, multiple linear regression analysis,  t-test  and  F-test  as  well  as  the  coefficient  of  determination.  Based  on data  analysis,  the  results  showed  that  the  indicators  on  research  is  valid  and reliability.  Hypothesis  test  on  tangible,  responsiveness,  assurance  and  emphaty no effect significantly to consumer satisfaction. Hypothesis test of reliability has a positive and significant influence toward customer satisfaction.